Phospholamban phosphorylation, mutation, and structural dynamics: a biophysical approach to understanding and treating cardiomyopathy - Ablorh, Naa-Adjeley D. (Biophys Rev, 2015)
We review the recent development of novel biochemical and spectroscopic methods to determine the site-specific phosphorylation, expression, mutation, and structural dynamics of phospholamban (PLB), in relation to its function (inhibition of the cardiac calcium pump, SERCA2a), with specific focus on cardiac physiology, pathology, and therapy. In the cardiomyocyte, SERCA2a actively transports Ca(2+) into the sarcoplasmic reticulum (SR) during relaxation (diastole) to create the concentration gradient that drives the passive efflux of Ca(2+) required for cardiac contraction (systole). Unphosphorylated PLB (U-PLB) inhibits SERCA2a, but phosphorylation at S16 and/or T17 (producing P-PLB) changes the structure of PLB to relieve SERCA2a inhibition. Because insufficient SERCA2a activity is a hallmark of heart failure, SERCA2a activation, by gene therapy (Andino et al. 2008; Fish et al. 2013; Hoshijima et al. 2002; Jessup et al. 2011) or drug therapy (Ferrandi et al. 2013; Huang 2013; Khan et al. 2009; Rocchetti et al. 2008; Zhang et al. 2012), is a widely sought goal for treatment of heart failure. This review describes rational approaches to this goal. Novel biophysical assays, using site-directed labeling and high-resolution spectroscopy, have been developed to resolve the structural states of SERCA2a-PLB complexes in vitro and in living cells. Novel biochemical assays, using synthetic standards and multidimensional immunofluorescence, have been developed to quantitate PLB expression and phosphorylation states in cells and human tissues. The biochemical and biophysical properties of U-PLB, P-PLB, and mutant PLB will ultimately resolve the mechanisms of loss of inhibition and gain of inhibition to guide therapeutic development. These assays will be powerful tools for investigating human tissue samples from the Sydney Heart Bank, for the purpose of analyzing and diagnosing specific disorders.